Benchmarking Costs of Financial Intermediation around the World - Calice, Pietro (World Bank, Washington, DC, 2018)
The costs of financial intermediation have important consequences for financial development. Using bank-level data for 160 countries during 2005-14, this paper analyzes the composition and sources of bank net interest margins. First, it uses an accounting decomposition framework to provide summary statistics on the size of net interest margins and highlight the cost and profit components in countries, regions, and income groups. Second, it uses regression analysis to examine the underlying bank-level, structural, macroeconomic, and institutional determinants of net interest margins. Finally, the paper uses the results of the econometric analysis to construct country-level bar charts of relative contributing factors to financial intermediation costs. The results provide evidence-based guidance on key areas of structural reforms to reduce the costs of financial intermediation.